Hydrothermal Synthesis of High-Yield Red Fluorescent Carbon Dots with Ultra-Narrow Emission by Controlled O/N Elements - Xian, Yingmei (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.